2022
DOI: 10.3389/fphar.2022.1023704
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of all-oral and injectable-containing, bedaquiline-based long treatment regimen for pre-XDR tuberculosis in Vietnam

Abstract: Background: The World health organization (WHO) recently recommended standardized all-oral shorter regimens for rifampicin resistant Tuberculosis (RR-TB). For highly resistant Tuberculosis patients such as pre-XDR-TB: RR-TB plus additional resistance to fluoroquinolones (FQ), the 6–9-months bedaquiline (bedaquiline)-based regimens or BDQ-based long regimens are recommended. The role of second-line injectable (SLI) drugs in the treatment of drug resistant TB is restricted because of safety concerns. Nevertheles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In total, 41 studies are included in the updated version of this review. The studies [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] were divided into two groups: 36 observational studies including a total of 9,934 patients, and 5 experimental studies including a total of 468 patients. The patient’s mean age was 36.2 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 41 studies are included in the updated version of this review. The studies [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] were divided into two groups: 36 observational studies including a total of 9,934 patients, and 5 experimental studies including a total of 468 patients. The patient’s mean age was 36.2 years.…”
Section: Resultsmentioning
confidence: 99%
“…A meta -analysis was conducted in 2021 that pooled the results of these studies [21] . However, results from additional well-designed observational and experimental studies were published [19] , [20] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] . To better analyze the effectiveness and safety of bedaquiline in MDR-TB, we conducted an updated meta -analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 16 17 ] However, some researchers reported the mean age group of patients of MDR-TB on the higher side in the fifth decade of life which might be probably due to variations in socio-demographic patterns between countries [ Table 2 ]. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] Nguyen reported culture conversion to negative in 60% and 86.7% of patients at 2 and 6 months, respectively, while Kim J reported culture conversion to negative in 45.7% and 60% at 4 and 8 months, respectively. [ 18 20 ] Khan et al . [ 23 ] in their study reported 85.5% culture conversion at 6 months duration of treatment in MDR-TB patients.…”
Section: Discussionmentioning
confidence: 99%